Topics on the Na+/Ca2+ Exchanger: Involvement of Na+/Ca2+ Exchanger in the Vasodilator-Induced Vasorelaxation - Junji Nishimura (Elsevier, 2006)
Many kinds of vasodilators induce relaxation of the vascular smooth muscle cells (VSMCs) through the production of cyclic AMP (cAMP) or cyclic GMP (cGMP). The relaxant effects mediated by these second messengers are thought to be mainly due to the decrease in intracellular Ca2+ concentration ([Ca2+]i), as well as the decrease in Ca2+ sensitivity of the contractile apparatus of VSMCs. To explain the cAMP- or cGMP-mediated decrease in [Ca2+]i, several mechanisms have been proposed, including the inhibition of Ca2+ influx due to a hyperpolarization, a stimulation of Ca2+ uptake into the intracellular store, and an increase in Ca2+extrusion from VSMCs by stimulation of sarcolemmal Ca2+-pump. VSMCs have two major systems for Ca2+ extrusion, namely, sarcolemmal Ca2+-pump and Na+/Ca2+ exchanger (NCX). However, the involvement of NCX in the vasodilator-induced relaxation of VSMCs has not been well established. In this article, the possible involvement of NCX in the vasodilator-induced relaxation of VSMCs will be reviewed. Keywords:: cyclic AMP, cyclic GMP, intracellular Ca2+ concentration, Na+/Ca2+ exchanger, vascular smooth muscle